2002
DOI: 10.1104/pp.005637
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Invertase Expression Is an Early Target of Drought Stress during the Critical, Abortion-Sensitive Phase of Young Ovary Development in Maize

Abstract: To distinguish their roles in early kernel development and stress, expression of soluble (Ivr2) and insoluble (Incw2) acid invertases was analyzed in young ovaries of maize (Zea mays) from 6 d before (Ϫ6 d) to 7 d after pollination (ϩ7 d) and in response to perturbation by drought stress treatments. The Ivr2 soluble invertase mRNA was more abundant than the Incw2 mRNA throughout pre-and early post-pollination development (peaking at ϩ3 d). In contrast, Incw2 mRNAs increased only after pollination. Drought repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
197
1
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(212 citation statements)
references
References 64 publications
11
197
1
3
Order By: Relevance
“…A second possibility is that vacuolar-targeted IVR2, present in the ESR, is mis-localized to the cell wall. IVR2 has been localized to the pedicel region by in situ analysis (Andersen et al, 2002), and we have demonstrated a strong in situ hybridization signal for IVR2 transcript in the ESR at 5 DAP (Y. Wang and N.J. Bate, unpublished data). A third possibility is that ZM-INVINH1 functions to inhibit an as yet uncharacterized apoplastic invertase (INCW).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A second possibility is that vacuolar-targeted IVR2, present in the ESR, is mis-localized to the cell wall. IVR2 has been localized to the pedicel region by in situ analysis (Andersen et al, 2002), and we have demonstrated a strong in situ hybridization signal for IVR2 transcript in the ESR at 5 DAP (Y. Wang and N.J. Bate, unpublished data). A third possibility is that ZM-INVINH1 functions to inhibit an as yet uncharacterized apoplastic invertase (INCW).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in this gene result in miniature kernels (the mn1 mutation) and have a severely reduced endosperm (Cheng et al, 1996;Vilhar et al, 2002). Recently, the association of a IVR2, a soluble invertase expressed during early kernel development, with seed yield under conditions of limiting photosynthesis suggests that soluble invertases also play a significant role in providing hexose sugars to support cell division during the prestorage phase (Andersen et al, 2002), as has been previously suggested (Zinselmeier et al, 1999).…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Most notably, the multicellular nature of plant tissues makes it difficult to quantitatively evaluate the contribution of VIN in specific cell types. For example, decrease of VIN expression is associated with maize ovary abortion or reduction in its expansion (Andersen et al, 2002;McLaughlin and Boyer, 2004). The VIN gene Ivr2, however, is expressed in nucellus and vascular bundles of the pedicel deeply embedded within the pericarp (Andersen et al, 2002).…”
mentioning
confidence: 99%
“…High VIN expression or activity has been observed in a range of expanding tissues, including maize (Zea mays) ovaries (Andersen et al, 2002;McLaughlin and Boyer, 2004), grape (Vitis vinifera) berry (Davies and Robinson, 1996), carrot (Daucus carota) taproot (Tang et al, 1999), and sugar beet (Beta vulgaris) petioles (González et al, 2005). It is hypothesized that VIN may play a major role in plant cell expansion, a key step in plant cell development (González et al, 2005).…”
mentioning
confidence: 99%